Enzyme Aided Peeling and Membrane Removal of Local Mandarins (Citrus Suhuiensis) - Liu, Fanny (2004)
A combination of pectinases and cellulases are able to selectively alter the albedo and segment membrane structure of citrus fruits and, hence, aid the removal of the peel, adhering albedo layer and also the segment membrane. This study was camed out to determine the optimum conditions needed to peel local mandarins using pectinases (PeelzymB IV, Novozyme, Switzerland) and cellulases (CelluclastB 1 SL, Novozyme, Switzerland). The experiment variables were enzyme concentration, vacuum pressure and vacuum infusion time. In the first part of the experiment, the local mandarins were first scored fiom stem end to the blossom end followed by immersion in 1000 ml of enzyme solution at a set vacuum pressure and ambient temperature (27 f 1 OC). Only one parameter was varied in any one experiment. The latter part of the experiment was carried out using Response Surface Methodology (RSM) to determine the optimum combinations of enzyme concentration, vacuum pressure and vacuum infusion time to aid enzymatic segment membrane removal. Echip software was employed in the experimental design, calculate equations and statistical analysis. PeelzymB IV at 0.4 % vlw, 650 mm Hg vacuum and 16 minutes of vacuum time were found to be optimal for peel removal.The enzyme-peeled h i t s were judged by the panellists using three different sensory tests to ascertain its appeal to consumers. A significant (P< 0.05) difference between enzyme-peeled and hand-peeled segments was found, with the panelists preferring the enzyme-peeled segments. Celluclast@ 1.5L at 4.52 % vlw, vacuum pressure at 370 mm Hg for 9 minutes was found to be optimal. After segment membrane removal, the membraneless local mandarin segments were then placed in different concentrations of sugar solutions to gauge consumer acceptance. Different sugar concentrations were used to emulate commercially available canned mandarin segments. Although varying concentrations of sugar solutions were used, the colour, odour, firmness, presence of adhering segment membrane and segment integrity were not affected as there was no significant (P<0.05) difference among the samples. It was also observed that local mandarins stored in 15 %rix was the preferred sugar concentration. As an overview, enzyme-peeled segments were found to be much more appealing as it had a much more intense orange colour, was firm with no loss of segment integrity, hence, was very well accepted by the panelists. Thus, enzyme aided peeling has a great potential as an alternative method to replace conventional methods of peeling.